Single particle aerosol mass spectrometry of coal combustion particles associated with high lung cancer rates in Xuanwei and Fuyuan, China. (November 2017) - Lu, Senlin; Tan, Zhengying; Liu, Pinwei; Zhao, Hui; Liu, Dingyu; Yu, Shang; Cheng, Ping; Win, Myat Sandar; Hu, Jiwen; Tian, Linwei; Wu, Minghong; Yonemochi, Shinich; et al.
Abstract: Coal combustion particles (CCPs) are linked to the high incidence of lung cancer in Xuanwei and in Fuyuan, China, but studies on the chemical composition of the CCPs are still limited. Single particle aerosol mass spectrometry (SPAMS) was recently developed to measure the chemical composition and size of single particles in real-time. In this study, SPAMS was used to measure individual combustion particles emitted from Xuanwei and Fuyuan coal samples and the results were compared with those by ICP-MS and transmission electron microscopy (TEM). The total of 38, 372 particles mass-analyzed by SPAMS can be divided into 9 groups based on their chemical composition and their number percentages: carbonaceous, Na-rich, K-rich, Al-rich, Fe-rich, Si-rich, Ca-rich, heavy metal-bearing, and PAH-bearing particles. The carbonaceous and PAH-bearing particles are enriched in the size range below 0.56 μm, Fe-bearing particles range from 0.56 to 1.0 μm in size, and heavy metals such as Ti, V, Cr, Cu, Zn, and Pb have diameters below 1 μm. The TEM results show that the particles from Xuanwei and Fuyuan coal combustion can be classified into soot aggregates, Fe-rich particles, heavy metal containing particles, and mineral particles. Non-volatile particles detected by SPAMS could also be observed with TEM. The number percentages by SPAMS also correlate with the mass concentrations measured by ICP-MS. Our results could provide valuable insight for understanding high lung cancer incidence in the area. Highlights: Size distributions of particles with different component from coal combustion are different. Non-volatile single particles can be measured by aerosol mass spectrometry (SPAMS) and transmission electron microscopy (TEM). Number percentages by SPAMS correlate with mass concentrations by ICP-MS.